2022
DOI: 10.1186/s13058-022-01530-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on cognitive function after chemotherapy in patients with breast cancer: a randomized controlled trial (PAM study)

Abstract: Background Up to 60% of breast cancer patients treated with chemotherapy is confronted with cognitive problems, which can have a significant impact on daily activities and quality of life (QoL). We investigated whether exercise training improves cognition in chemotherapy-exposed breast cancer patients 2–4 years after diagnosis. Methods Chemotherapy-exposed breast cancer patients, with both self-reported cognitive problems and lower than expected pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 53 publications
5
52
0
Order By: Relevance
“…Four studies investigated exercise interventions including a group‐based community exercise program, 81 walking, 79 breathing with light exercise 82 and aerobic exercise with Nordic power walking 80 . A community‐based exercise program found no statistically significant improvements in subjectively measured cognitive function 81 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies investigated exercise interventions including a group‐based community exercise program, 81 walking, 79 breathing with light exercise 82 and aerobic exercise with Nordic power walking 80 . A community‐based exercise program found no statistically significant improvements in subjectively measured cognitive function 81 .…”
Section: Resultsmentioning
confidence: 99%
“…found that a home‐based self‐implemented walking intervention over 12 weeks improved memory capacity ( p = 0.03) as measured by the Welschler Adult Intelligence Scale (WAIS). Koevoets et al 80 . conducted an RCT investigating the impact of aerobic exercise with Nordic power walking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomized controlled study found a significant effect of reduced depression and improved sleep quality on the relationship between motor functions and COI in older adults. 13 It has also been found that regular PE improved sleep quality and alleviated depression, 14 which in turn have been indicated to mitigate the development of COI. 13 Studies have also shown that there is a marked negative relationship between sleep quality and depression 15 and that low levels of sleep quality can also contribute to psychological and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%